Pivotal aspects of organology of Stradivarius violins and their contribution to higher formant frequencies - Bain, Marina Rose (2025)
This paper will explore the organology of Stradivarius violins and how such aspects affect their acoustic quality and thus the formant frequencies. A master luthier is in his workshop in Cremona, known by the name of Antonio Stradivari (1644-1737). He is sat at his workbench masterfully carving the scroll of his next violin, which will be played by the virtuosi of not only his era, but for centuries to come. In Italy between the sixteenth and eighteenth centuries, Cremona was highly regarded for violin making, with many master luthiers working there and these luthiers are still famous centuries later. Luthiers and scholars today have the highest respect for the existing Cremonese instruments, especially those made by Antonio Stradivari, whose prolific output surpassed the quantity of other makers, yet with detailed and masterful craftsmanship. In my research I aim to explore which aspects of organology may have contributed to the acoustic quality of Stradivarius violins by investigating what lies behind the higher formant frequencies exhibited by Stradivarius violins by bringing together research and analysis previously conducted on the organology of Stradivarius violins, to shed light on why or how these formant frequencies are present. I will present a multi-faceted approach assessing several aspects of organology of Stradivarius violins which may contribute to the acoustic quality and thus formant frequencies of Stradivarius violins. Previous research by scholars has mostly concentrated on individual scientific research which has focused on one single aspect of organology of Cremonese and Stradivarius violins. There has been little research thus far focused on multi-faceted approaches on the organology of Stradivari violins which compares and draws links between the scientific studies on the organology of Stradivarius violins. If the science of Stradivarius violins is understood, we can get closer to understanding what creates the acoustic quality of these valuable instruments.